Current ideas about pathogenesis and treatment of so-called essential epilepsy - Bambaren, Carlos A. (1920)
Disclose in our environment the notion of plurality of epilepsy, raise a better study of these patients improving their condition and their future, arouse the curiosity of scholars, because in the course of this work we will expose many unknowns that still exist in the genesis and treatment of this disease, which need investigation; gather as comprendiosa which in recent times has come to our knowledge of pathogenesis and treatment of epilepsy, such is the longing we have had to make this study suggested moments of earnest scientific meditation contemplating the protean manifestations of this disease and therapeutic uncertainties, appreciated very closely by our particular interest in nervous and mental diseases and the number of years that we've practiced at the Hospital for the Insane and of which we have not departed yet.